Chad Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
The auditing profession in Chad is characterized by the existence of numerous practitioners who provide accounting and auditing services illegally, in violation of community regulations, and whose qualifications often do not meet the international standards. To date, Chad has not yet set up a national association of chartered accountants. One of the most pressing areas in transposing community texts relates to the establishment of a national association of chartered accountants, whose existence is essential for the development and practice of the accountancy profession in Chad. It is also important for consolidating accounting and auditing processes, improving the quality of financial reporting, facilitating access to credit and supporting foreign direct investors, as well as improving the competitiveness of national businesses. With regard to the accounting standards, the Uniform Act (UA) organizing and harmonizing accounting systems for businesses, as well as the accounting chart of accounts and the provisions put in place by the Commission Bancaire d'Afrique Centrale (COBAC) and the Conference Interafricaine des Marches d'Assurances (CIMA) code, there has been very little change since their entry into force towards the end of the 1990s. This is due to shortcomings in the functioning of the regional bodies in charge of ensuring that these texts were updated in line with changes in the accounting, economic, and legal fields. Looking ahead, the major areas of focus in seeking to strengthen the legal and regulatory framework governing accountancy and auditing professions in Chad are the following: (i) the reclassification of CEMAC licensed accounting technicians in Chad in the category of public accountants, in accordance with community regulations, (ii) the establishment of a national association of chartered accountants, (iii) the proper functioning of the national accounting standards commission, (iv) the adoption of auditing professional standards and a code of ethics in line with those established by International Federation of Accountants, or IFAC independent standard-setting board, (v) the strengthening of initial training through the improvement of the quality of the national curriculum and by drafting a continuous professional training plan, and (iv) the capacity building of the Court of Accounts to enable it implement INTOSAI auditing standards in order to ensure proper supervision of public enterprises.